2016
DOI: 10.1186/s12888-016-1099-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric readmissions and their association with environmental and health system characteristics: a systematic review of the literature

Abstract: BackgroundPsychiatric readmissions have been studied at length. However, knowledge about how environmental and health system characteristics affect readmission rates is scarce. This paper systemically reviews and discusses the impact of health and social systems as well as environmental characteristics for readmission after discharge from inpatient care for patients with a psychiatric diagnosis.MethodsComprehensive literature searches were conducted in the electronic bibliographic databases Ovid Medline, PsycI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 45 publications
3
51
1
Order By: Relevance
“…Our research yielded results similar to the findings of previous studies showing that high‐risk patients or patients with more diverse comorbidities present more adverse outcomes than other patients . Regarding socioeconomic status, our study demonstrated that patients with a regular job had fewer adverse outcomes than those without a regular job, which is similar to previous research showing that high quality‐of‐life scores positively correlate with the employment status of patients with schizophrenia …”
Section: Discussionsupporting
confidence: 90%
“…Our research yielded results similar to the findings of previous studies showing that high‐risk patients or patients with more diverse comorbidities present more adverse outcomes than other patients . Regarding socioeconomic status, our study demonstrated that patients with a regular job had fewer adverse outcomes than those without a regular job, which is similar to previous research showing that high quality‐of‐life scores positively correlate with the employment status of patients with schizophrenia …”
Section: Discussionsupporting
confidence: 90%
“…Although length of stay might reflect treatment difficulties, it is likely that a court will order a discharge only when a patient has recovered, so on returning to the community, both long‐ and short‐stay patients should be similar in this respect. That said, Kalseth, Lassemo, Wahlbeck, Haaramo, and Magnussen () reported a negative correlation between length of inpatient stay and subsequent readmission.…”
Section: Discussionmentioning
confidence: 99%
“…With hospital readmission as an important quality indicator, the 2010 Affordable Care Act developed the Hospital Readmissions Reduction Program, which requires reduced payments from Medicare and Medicaid to hospitals with excess readmissions for certain medical diagnoses . Although this program did not target psychiatric readmissions, these occur at much higher rates and are increasingly scrutinized from both a quality and cost standpoint.…”
Section: Legal and Ethical Issuesmentioning
confidence: 99%
“…Affordable Care Act developed the Hospital Readmissions Reduction Program, which requires reduced payments from Medicare and Medicaid to hospitals with excess readmissions for certain medical diagnoses. 43 Although this program did not target psychiatric readmissions, these occur at much higher rates and are increasingly scrutinized from both a quality and cost standpoint. Many of the risk factors for readmission that are peripheral to the primary medical diagnosis of patients are the primary risk factors for psychiatric hospitalization, including mental illness diagnosis, substance use, and a poor socioeconomic situation.…”
Section: Payment Issuesmentioning
confidence: 99%